The Feminization U in South Africa: Economic Structure and Women's Labor Force Participation. - Roncolato, Leanne (Feminist Economics, 2016)
The feminization U theory claims that women’s labor force participation drops during the initial phase of industrialization and rises once a certain level of development is reached. This paper is the first to exploit the diversity in economic structure across municipalities to consider the shape of the feminization U in a developing country. Using data from South Africa’s 2007 Community Survey, this study investigates whether a feminization U exists. Results reveal a U-shaped relationship between the share of nonagricultural employment and women’s probability of being in the labor force. Results show that the exclusion of informal urban employment leads to an overestimation of the U slope and part of the decline in women’s labor force participation during early structural change is likely related to household and care constraints. A U-shaped relationship is not found between the share of households with electricity and women’s probability of being in the labor force.